Immobilization and evaluation of some clinical parameters for free-ranging elephants (Loxodonta africana) in southern Tanzania - Mpanduji, Donald; Hildebrandt, Thomas; Fyamagwa, Robert; Wiik, Harald; Siege, Ludwig; Baldus, Rolf; Bittegeko, Salvatory; Hermes, Robert; Hahn, Rudolf; Hofer, Heribert; Göritz, Frank (Pachyderm, 2003)
Physiology and blood chemistry of a dozen adult elephant during a radio collaring operation intended to track seasonal movement and home ranges in the Selous-Naissa wlildlife corridor in southern Tanzania. 8 of the animals were anaesthesized with M99 and 4 were given M99 and Stresmil (one cow was given reversal drugs without being radiocollared and one bull died, 10 animals were successfully radio collared). Physiology and blood chemistry parameters are discuss and outlined in tables comparing them with parameters found in the literature and/or recorded by other researchers. The authors discuss the need to plan the darting progremme carefully, and to monitor the anaesthesized animals with animal health and welfare in mind.